2011
DOI: 10.1108/02632771111101313
|View full text |Cite
|
Sign up to set email alerts
|

Balancing collaboration and privacy in academic workspaces

Abstract: Purpose -The purpose of this paper is to evaluate the effectiveness of two different academic office environments in supporting collaboration and privacy. Design/methodology/approach -The approach takes the form of case studies involving post-occupancy questionnaire surveys of academic occupants. Findings -The combi-office design was found to be associated with higher levels of occupant satisfaction than the open-plan office design, with respect to support for collaboration and privacy.Research limitations/imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 16 publications
(14 reference statements)
1
47
0
Order By: Relevance
“…While the results support the view that distractions can lead to impaired collaboration and stress symptoms, the exact mechanisms still remain unclear. Collaboration might have been diminished because of impaired inter-personal relations (Bodin Danielsson et al, 2015) or simply because interaction was decreased, for example, due to a concern of disturbing others (Parkin, Austin, Pinder, Baguley, & Allenby, 2011). In addition, impaired collaboration may not be a source of stress but may rather reflect diminished social support that moderates the effects of environmental and other stressors (Karasek & Theorell, 1990;Viswesvaran et al, 1999).…”
Section: The Role Of Distractionsmentioning
confidence: 99%
“…While the results support the view that distractions can lead to impaired collaboration and stress symptoms, the exact mechanisms still remain unclear. Collaboration might have been diminished because of impaired inter-personal relations (Bodin Danielsson et al, 2015) or simply because interaction was decreased, for example, due to a concern of disturbing others (Parkin, Austin, Pinder, Baguley, & Allenby, 2011). In addition, impaired collaboration may not be a source of stress but may rather reflect diminished social support that moderates the effects of environmental and other stressors (Karasek & Theorell, 1990;Viswesvaran et al, 1999).…”
Section: The Role Of Distractionsmentioning
confidence: 99%
“…Their study also indicated that individual workstations were overwhelmingly preferred by employees for collaborative as well as other types of work. Parkin et al (2011)…”
Section: Workplace Design and Communication And Collaborationmentioning
confidence: 99%
“…propose an integrated framework to explain how the physical and social characteristics of a setting influence informal interaction. A workspace invites interaction only if it balances proximity, privacy and permission (Fayard & Weeks, 2011;Parkin et al, 2011). Moreover, some authors emphasize the importance of spaces that are not dedicated to the organization's core activity but where interactions may occur (Goffman, 1997;Allen & Henn, 2007;van Marrewijk & Yanow, 2010), such as corridors (Hurdley, 2010;, or coffee machines and photocopier rooms .…”
Section: Physical Settings and Social Designation Of Workpacesmentioning
confidence: 96%